Mahdi Elmandjra and the future of the Muslim world - Wan Fariza Alyati Wan Zakaria, (Universiti Kebangsaan Malaysia, 2013)
The increasing problems and challenges facing the Muslims and the Muslim world nowadays have raised serious concern about the future of the Muslims and the Muslim World among many Muslim scholars. The post-Iranian Islamic Revolution in 1979 had always been seen as the landmark of the rising discourses over the future of Islam, Muslims and the Muslim world. Mahdi Elmandjra, a prominent sociologist and futurist, is one of the Muslim scholars who consistently discuss about the issue and urge the Muslims to take responsibility to create a better future in a systematic way and not to fall into the vicious cycle of misfortunes. This paper aims at discussing Elmandjra’s views on this issue and underscoring the contribution and significance of such discourse within contemporary development.